A sensitive and selective HPLC–MS3 method for therapeutic drug monitoring of meropenem and its validation by comparison with HPLC–MS2 methods. Issue 10 (18th March 2022) - Cao, Haiwei; Yin, Lei; Cao, Haihuan; Guo, Haiyang; Ren, Wenbo; Li, Yanyan; Huang, Jing
Abstract : Meropenem, a representative β‐lactam antibiotic, is widely used to treat complicated and serious infections. Therefore, it is of great significance to monitor the plasma drug concentration for individualized antimicrobial therapy. This study first describes the development and validation of high‐performance liquid chromatography–tandem mass spectrometry cubed method for monitoring meropenem in human plasma. Protein precipitation with methanol and a chromatographic analysis time of 7 min make this method simple and of high throughput. Meropenem was extracted from human plasma with recoveries >94.1%. Calibration curves were linear ( R 2  > 0.995) in the concentration range of 0.5–50 μg/mL. Overall accuracy and precision did not exceed 8.0% as well as no significant matrix effect was observed. The novelty of this method is that the triple‐stage mass spectrometry technology improves the selectivity and sensitivity. A comparison of the presented method and traditional liquid chromatography–tandem mass spectrometry method was assessed in 44 patients treated with meropenem and Passing–Bablok regression coefficients and Bland–Altman plots showed that no significant difference between the two methods. So the triple‐stage mass spectrometry method developed in this study is appropriate and practical for the monitor of meropenem in the daily clinical laboratory practice.